A map of Pleistocene aeolian deposits in Western Europe, with special emphasis on France. (November 2016) - Bertran, Pascal; Liard, Morgane; Sitzia, Luca; Tissoux, Hélène
ABSTRACT: The Land Use and Cover Area frame Statistical survey (LUCAS) database on topsoil properties in Europe was used to map aeolian deposits. The points which satisfy the grain‐size criteria of coversands, loess and transitional facies were extracted from the rasters of predicted soil texture established by kriging of the LUCAS data by Ballabio et al . (2016 ). A comparison with already available maps, derived from a conventional field approach, shows a good fit in most of the tested areas. The new map, however, suggests a greater extension of loess, which seems related to the inclusion of thin loess covers, usually omitted by conventional mapping, and the presence of previously unmapped areas due to lack of survey or misinterpretation. The main source of aeolian particles corresponds to glacio‐fluvial sediments at the margin of the Scandinavian and Alpine ice sheets. Coversands and loess form a broad band across northern Europe, and in the Rhône, Rhine and Danube valleys. Large areas on the outskirts of these deposits also received a significant loess contribution, which has been reworked in slope deposits. Conversely, southern Europe is characterized by much less loess accumulation. The Atlantic coast has transgressive dune fields that penetrate inland to varying degrees.